Kebijakan Pemerintah Kota Surabaya Terkait Izin Pemakaian Tanah Milik Es Krim PT. Z - Cindy Inez Hoarisan; Emilda Aisyafuri; Carolina Septiani (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
- The Surabaya City Government issued Surabaya City Regional Regulation Number 3 of 2016 concerning Land Use Permits (IPT). This Regional Regulation provides certainty regarding green letters which are assets from the Surabaya City Government. The Surabaya City Government can collect retribution or rent money from the tenant, in this case the citizen who owns the green letter. This research uses a qualitative approach, where this research uses a natural setting with the intention of interpreting the phenomena that occur and is carried out by involving existing methods. The result of the writing about this case study is that the right to enjoy the permit over the use of the land is still applies for Ice Cream Z's ownership if the re-submission process is approved, because the Regional Regulation does not explain that the end of contact does not include the end of IPT, beside that the requirements for rejection of an applications issued by the Surabaya City Government do not have an appropriate legal basis.